Paediatric patients with heterozygous familial hypercholesterolaemia treated with evolocumab for 80 weeks (HAUSER-OLE): a single-arm, multicentre, open-label extension of HAUSER-RCT. Issue 10 (October 2022) - Santos, Raul D; Ruzza, Andrea; Hovingh, G Kees; Stefanutti, Claudia; Mach, François; Descamps, Olivier S; Bergeron, Jean; Wang, Bei; Bartuli, Andrea; Buonuomo, Paola Sabrina; Greber-Platzer, Susanne; Luirink, Ilse; et al.
Summary: Background: The HAUSER-RCT study showed that 24 weeks of evolocumab (a proprotein convertase subtilisin/kexin type 9 [PCSK9] inhibitor) in paediatric patients with heterozygous familial hypercholesterolaemia was safe and improved lipid parameters compared to placebo. Here, we aimed to evaluate the safety and efficacy of evolocumab in this population for an additional 80 weeks. Methods: HAUSER-OLE was an 80-week, single-arm, open-label extension of HAUSER-RCT, a randomised controlled trial, and was conducted at 46 centres in 23 countries. Paediatric patients aged 10–17 years with heterozygous familial hypercholesterolaemia who completed 24 weeks of monthly treatment with subcutaneously administered placebo or 420 mg evolocumab in HAUSER-RCT with no serious treatment-emergent adverse events were eligible to enrol in HAUSER-OLE. All patients received open-label subcutaneous evolocumab 420 mg monthly with background statins with or without ezetimibe for 80 additional weeks. The primary endpoint was treatment-emergent adverse events. Efficacy was evaluated by changes in lipids from the baseline of HAUSER-RCT to the end of HAUSER-OLE (104 weeks). This study is registered with ClinicalTrials.gov (NCT02624869 ) and is now completed. Findings: Between Sept 10, 2016, and Nov 25, 2019, 157 patients were enrolled in HAUSER-RCT and received randomised treatment; 150 continued to HAUSER-OLE, received evolocumab treatment, and were included in the full analysis set, presented here. 146 (97%) of 150 patients completed the open-label extension. The incidence of treatment-emergent adverse events in HAUSER-OLE was 70% (105 of 150). Overall, the most common treatment-emergent adverse events were nasopharyngitis (22 [15%] of 150), headache (14 [9%]), and influenza-like illness (13 [9%]). Serious treatment-emergent adverse events occurred in four (3%) of 150 patients (perforated appendicitis and peritonitis, wrist fracture, anorexia nervosa, and headache); none was considered related to evolocumab. No treatment-emergent adverse events led to treatment discontinuation. At week 80, the mean percentage change from baseline in LDL cholesterol was –35·3% (SD 28·0). Interpretation: After 80 weeks of treatment, evolocumab was safe, well tolerated, and led to sustained reductions in LDL cholesterol in paediatric patients with heterozygous familial hypercholesterolaemia. When lipid goals cannot be achieved with conventional treatments, evolocumab is an effective add-on therapy in paediatric patients. Funding: Amgen. Translations: For the French, Spanish, Spanish, Portuguese, Italian and Dutch translations of the abstract see Supplementary Materials section.